Dynamics of life course family transitions in Germany: Exploring patterns, process and relationships - Raimond Maurer; Sehrish Usman (Leibniz Institute for Financial Research SAFE, 2023)
This paper explores dynamics of family life events in Germany using discrete time event history analysis based on SOEP data. We find that higher educational attainment, better income level, and marriage emerge as salient protective factors mitigating the risk of mortality; better education also reduces the likelihood of first marriage whereas, lower educational attainment, protracted period, and presence of children act as protective factors against divorce. Our key finding shows that disparity in mean life expectancies between individuals from low- and high-income brackets is observed to be 9 years among males and 6 years among females, thereby illustrating the mortality inequality attributed to income disparities. Our estimates show that West Germans have low risk of death, less likelihood of first marriage, and they have a high risk of divorce and remarriage compared to East Germans.
Keywords: C13; C34; J12; 330; Family dynamics; Life Events; Hazard estimation; Life course transitions